2020
DOI: 10.1037/scp0000234
|View full text |Cite
|
Sign up to set email alerts
|

Underdeveloped affective maturity and unintegrated psychosexual identity as contributors to clergy abuse and boundary violations: Clinical observations from residential treatment of Roman Catholic clergy at the Southdown Institute.

Abstract: Nothing has dominated public discourse about the Roman Catholic Church as much as the fallout from sexual abuse of minors. Because some of the publicly available knowledge about psychological contributors to abuse and boundary violations at the hands of Catholic clergy and religious is based on inaccurate assumptions and information, this article, which is based on archival assessment and treatment data as well as clinical observations, aims to contribute evidence-based, clinical data. Whereas the numbers of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Another challenge to seeking psychological services is the belief that going to confession suffices for one’s wrongful or problematic behavior. Kappler et al (2020) argued that the Sacrament of Reconciliation is often relied upon as a means of correcting for any missteps regarding the tendency to exercise undue control over one’s sexual impulses. They noted that confession limits any significant exploration of one’s underlying sexual interests and dynamics.…”
Section: Challenges To Faith-based Groups Seeking Psychological Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another challenge to seeking psychological services is the belief that going to confession suffices for one’s wrongful or problematic behavior. Kappler et al (2020) argued that the Sacrament of Reconciliation is often relied upon as a means of correcting for any missteps regarding the tendency to exercise undue control over one’s sexual impulses. They noted that confession limits any significant exploration of one’s underlying sexual interests and dynamics.…”
Section: Challenges To Faith-based Groups Seeking Psychological Servicesmentioning
confidence: 99%
“…Fox et al (2017) referred to this challenge as spiritual bypass. Kappler et al (2020) described it as using spirituality to shield oneself from experiencing one’s emotions and taking responsibility for one’s actions. Another challenge relates to those clergy and religious personnel who have been swept up in the wave of ideologies and conspiracy theories, which further casts psychological treatment or services in negative light.…”
Section: Mental Health Stigma Reduces Search For Psychological Servicesmentioning
confidence: 99%
“…Clinical observations with this population have indicated that, in addition to the experience of depression and anxiety, loneliness may be an important research variable, as increasing number of priests across Canada live alone. Furthermore, religious coping has emerged as an important variable in the psychological well-being of priests (Kappler et al 2020). In addition, as a group, priests frequently associate their personal identity with their ministry and their capacity to engage in ministry.…”
Section: The Present Studymentioning
confidence: 99%